2007
DOI: 10.4103/0970-1591.32076
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of urinary tract obstruction due to imperforate hymen in an 11-month-old infant

Abstract: Variations in the anatomy of the hymen are common and imperforate hymen is an extreme manifestation. In spite of the recommendations for early inspection of the external genitalia, hymenal malformations escape diagnosis until the time of menarche. Rarely, female infants with imperforate hymen present with urologic complications. We would like to present an unusual case of urinary retention in an 11-month-old female infant due to imperforate hymen. This infant was successfully treated surgically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 4 publications
0
20
0
5
Order By: Relevance
“…Es de gran importancia la realización de una exploración física detallada, pues su omisión puede conllevar un retraso en el diagnóstico, lo cuál se asocia con la posible aparición de patologías asociadas tales como endometriosis, adenosis vaginal, infecciones urinarias, retención urinaria e, incluso, hidronefrosis bilateral con fallo renal, hematosalpinx y hemoperitoneo, y pudiendo llegar a comprometer la fertilidad futura de la paciente (12)(13)(14).…”
Section: Discussionunclassified
“…Es de gran importancia la realización de una exploración física detallada, pues su omisión puede conllevar un retraso en el diagnóstico, lo cuál se asocia con la posible aparición de patologías asociadas tales como endometriosis, adenosis vaginal, infecciones urinarias, retención urinaria e, incluso, hidronefrosis bilateral con fallo renal, hematosalpinx y hemoperitoneo, y pudiendo llegar a comprometer la fertilidad futura de la paciente (12)(13)(14).…”
Section: Discussionunclassified
“…Este retraso en el diagnóstico puede ocasionar la aparición de patologías, como endometriosis, adenosis vaginal, infecciones urinarias, retención urinaria e, incluso, hidronefrosis bilateral con falla renal, hematosalpinx y hemoperitoneo, y puede llegar a comprometer la fertilidad. [13][14][15] La conclusión principal de este caso es destacar la importancia de la exploración física completa, incluidos los genitales externos, que siempre debe estar incorporada a la sistemática del pediatra. La simple inspección, como en esta paciente, puede dar la clave del diagnóstico, y evitar la demora en el tratamiento y sus posibles secuelas.n BIBLIOGRAFÍA…”
Section: Discussionunclassified
“…Although a review of literature revealed at least 41 similarly reported cases, this is a condition that can still remain unrecognised by the referring physician 1 2 4–22…”
Section: Discussionmentioning
confidence: 99%